2012
DOI: 10.1097/hjh.0b013e3283567645
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of cilnidipine and amlodipine on cardiac remodeling and diastolic dysfunction in Dahl salt-sensitive rats

Abstract: Cilnidipine attenuated LV fibrosis and diastolic dysfunction as well as LV concentricity to a greater extent than did amlodipine in Dahl salt-sensitive rats. The superior cardioprotective action of cilnidipine is likely attributable, at least in part, to the greater antioxidant and anti-inflammatory effects associated with inhibition of cardiac RAS gene expression observed with this drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 52 publications
2
27
0
Order By: Relevance
“…In the present study, UUO rats were treated with cilnidipine or amlodipine at the dose of 3 mg·kg Ϫ1 ·day Ϫ1 for 14 days. Several previous reports demonstrated that cilnidipine and amlodipine had a lowering effect of blood pressure to a similar extent at the dose used in this study (3 mg·kg Ϫ1 ·day Ϫ1 ) in hypertensive rats (12,25,26). Previous pharmacological study also demonstrated that cilnidipine and amlodipine inhibited L-type Ca channel current to a similar extent using a whole cell patch-clamp technique (29).…”
Section: Discussionsupporting
confidence: 68%
“…In the present study, UUO rats were treated with cilnidipine or amlodipine at the dose of 3 mg·kg Ϫ1 ·day Ϫ1 for 14 days. Several previous reports demonstrated that cilnidipine and amlodipine had a lowering effect of blood pressure to a similar extent at the dose used in this study (3 mg·kg Ϫ1 ·day Ϫ1 ) in hypertensive rats (12,25,26). Previous pharmacological study also demonstrated that cilnidipine and amlodipine inhibited L-type Ca channel current to a similar extent using a whole cell patch-clamp technique (29).…”
Section: Discussionsupporting
confidence: 68%
“…In Dahl salt-sensitive rat model, Cilnidipine reduces relative wall thickness more than Amlodipine [48], Cilnidipine significantly improved LVMI than that of control CCBs group and Cilnidipine reduces LV mass index significantly after 3 months of the initiation of treatment whereas Amlodipine do so 6 months after the initiation of treatment, also corroborates with the result of present study [49,50].…”
Section: Discussionsupporting
confidence: 91%
“…Both body weight and food intake were monitored on a weekly basis. Systolic blood pressure (SBP) was also measured weekly with animals in the conscious state by indirect tail‐cuff plethysmography (BP‐98A; Softron, Tokyo, Japan) . An oral glucose tolerance test (OGTT) and an insulin tolerance test (ITT) were performed as described previously …”
Section: Methodsmentioning
confidence: 99%